THE ROLE OF LITERATURE IN ENHANCING ENGLISH LANGUAGE COMPETENCE - Behruzkhon Yuldoshev Behzod ugli (INTERNATIONAL JOURNAL OF SCIENCE-INNOVATIVE RESEARCH, 2025)
The article explores the importance of literature in the development of English language competence. It analyzes how literary texts contribute to the enrichment of vocabulary, grammatical awareness, communicative fluency, and intercultural understanding. The study highlights both the theoretical and practical aspects of integrating literature into language teaching, emphasizing its role in fostering linguistic, cultural, and cognitive development.